Tourism Village Community Participation: Forms, Benefits, Strategies and Barriers to Participation Towards a Sustainable Tourism Village - AMALINA, Wijhatun; LISTYORINI, Haniek (Journal of Tourism Economics and Policy, 2025)
Tourism villages in Indonesia are generally a form of rural community-based tourism that aims to benefit local communities, so the role of community participation is very important to preserve and promote local culture and traditions. This research aims to explore the importance of community participation in the development of Asinan Tourism villages, both benefits, strategies for fostering participation and obstacles to participation. The research method used was qualitative research with village government informants, tourism village institutions, tourism actors, MSME community groups, guides and transportation providers. The results of the study show that the people of Asinan village have participated through active participation in various institutions supporting tourist villages, as providers of attractions, amenities and accessibility. The benefits obtained are the preservation of traditions and culture, economic opportunities and environmental preservation. The strategy carried out in increasing participation is to provide an understanding of tourism villages, funding, training, community involvement in ideas and decisions, and increasing the role of village governments. Some of the obstacles to fostering community participation include lack of understanding of the benefits of tourism villages, reluctance to change, concerns about exploitation and lack of resources and infrastructure.